Uji Daya Hasil Kubis Bunga (Brassica oleracea L. var. Botrytis) Kultivar Larissa F1 Akibat Kombinasi Sistem Tanam Non Konvensional dan Cekaman pH Asam Larutan Nutrisi - Anne Venitya Septiawan; Rommy Andhika Laksono; Yayu Sri Rahayu (Universitas Respati Indonesia, 2025)
The main issues faced in current cultivation practices are the reduction of available land and the decline in production. One solution is to shift from conventional farming to non-conventional or urban farming systems, such as hydroponic wick systems and aeroponics. The success of hydroponic and aeroponic cultivation is strongly influenced by the plant’s ability to absorb nutrients, particularly the acidity level (pH) of the nutrient solution. This study aims to determine the best combination of non-conventional cultivation systems and acidic pH stress of nutrient solutions on the growth and yield of cauliflower (Brassica oleracea L. var. Botrytis) cultivar Larissa F1. The experiment used a single-factor Randomized Block Design (RBD) consisting of six treatments and four replications: hydroponic wick system + pH 4–5, pH 5–6, pH 6–7, and aeroponics + pH 4–5, pH 5–6, and pH 6–7. Data were analyzed using F-test and Duncan Multiple Range Test (DMRT) at a 5% significance level. The results showed that the combination of cultivation systems and acidic pH significantly affected plant height at 56 DAT, number of leaves at 42 DAT, leaf area, root length, fresh weight, curd diameter, curd height, curd weight, and trimmed curd weight. The best treatment was the wick system with pH 6–7, producing a curd height of 13.6 cm, plant fresh weight of 585.5 g, curd weight of 291.8 g, and trimmed curd weight of 277.6 g.